1996
DOI: 10.1088/0953-2048/9/2/008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of films prepared by laser ablation of precursor targets andex situthalliation

Abstract: Thin films of Tl 2 Ba 2 CaCu 2 O 8 (Tl-2212) were grown on LaAlO 3 (001) single crystals by excimer laser ablation using Tl-free Ba 2 CaCu 2 O x targets and subsequent ex situ thalliation. The thalliation process of the film precursor (Ba 2 CaCu 2 O x ) took place in an Al 2 O 3 crucible containing the precursor and Tl-2212 powder. The procedure was carried out at a temperature T a = 820-870 • C and under a reduced oxygen pressure p(O 2 ) = 20-400 Torr. The resulting Tl-2212 films were characterized by XRD, AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…A similar phenomenon was also reported by other groups (Hewat et al 1988, Sequeira et al 1988, Morosin et al 1991a, Chrzanowski et al 1996. According to Aselage et al (1992Aselage et al ( , 1994) the T1-2212 phase can be formed at 850°C by annealing Ba2CaCu20, precursors in T120 vapour in a wide range of pressures.…”
Section: 1supporting
confidence: 81%
See 1 more Smart Citation
“…A similar phenomenon was also reported by other groups (Hewat et al 1988, Sequeira et al 1988, Morosin et al 1991a, Chrzanowski et al 1996. According to Aselage et al (1992Aselage et al ( , 1994) the T1-2212 phase can be formed at 850°C by annealing Ba2CaCu20, precursors in T120 vapour in a wide range of pressures.…”
Section: 1supporting
confidence: 81%
“…However, defects always occur in the T1-2212 structure as have been reported. For example, T1 deficiency has been reported for bulk T1-2212 crystals (Hewat et al 1988, Sequeira et al 1988, Morosin et al 1991a, Aselage et al 1992) and for Ti-2212 thin films (Chrzanowski et al 1996, Zhang et al 1997. Some of the T1 ions could be substituted by Ca (Hiraga et al 1988, Kikuchi et al 1989, Morosin et al 1991a or Cu ions (Sasaki et al 1992).…”
mentioning
confidence: 97%
“…Since P (Tl 2 O) is much higher in equilibrium with Tl For a given Tl HTS phase, P (O 2 ), P (Tl 2 O) and thalliation time there is an optimum thalliation temperature. There is considerable evidence suggesting that reducing the oxygen partial pressure encourages the Tl(2223) phase to form at lower temperatures [46,53,54,63,[66][67][68]. Since reduced P (O 2 ) promotes melting, the reduction in annealing temperature is thought to result from a decrease in the temperature required to produce the liquid phase necessary for Tl(2223) formation [44,53].…”
Section: Thermodynamic and Kinetic Factors Affecting Thalliationmentioning
confidence: 99%
“…Yan et al [73,74] have fabricated Tl(2212) on LaAlO 3 substrates at temperatures between 720 and 760 • C by thalliating in pure Ar. Ex situ thalliation anneals in Ar atmospheres have also been used by O'Connor et al [75] to fabricate Tl(2212) thin films on LaAlO 3 substrates at temperatures of between 720 and 740 • C. Chrzanowski et al [66], in their study of 2212 film growth, found that films thalliated using P (O 2 ) values in the centre of the Tl(2212) stability region had the highest values of T c but that, for the highest values of J c , conditions near the Tl(2212)-Tl(2223) boundary were optimum. They studied the correlation between the superconducting properties of the films and the degree of cation disorder using Auger electron spectroscopy.…”
Section: Thermodynamic and Kinetic Factors Affecting Thalliationmentioning
confidence: 99%
See 1 more Smart Citation